2000
DOI: 10.1302/0301-620x.82b8.0821170
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in the diagnosis of fractures in children

Abstract: We compared the results of primary ultrasonographic examination of 163 children with 224 suspected fractures with the subsequent radiological findings. The aim was to assess the value of ultrasound in the diagnosis of fractures in children. We found a good correlation for fractures of the long bones of the upper and lower limbs. Ultrasound was most reliable for the detection of simple femoral and humeral diaphyseal fractures and fractures of the forearm. It was less dependable for compound injuries and fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 0 publications
2
42
0
3
Order By: Relevance
“…At least two longitudinal planes should be scanned, although an original description by Hü bner et al reported scanning in four longitudinal planes with transverse scans obtained as appropriate [23][24][25]. The cortex of the bone is seen as a homogenous, bright reflection of echoes with dorsal acoustic shadowing.…”
Section: Scanning Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…At least two longitudinal planes should be scanned, although an original description by Hü bner et al reported scanning in four longitudinal planes with transverse scans obtained as appropriate [23][24][25]. The cortex of the bone is seen as a homogenous, bright reflection of echoes with dorsal acoustic shadowing.…”
Section: Scanning Techniquementioning
confidence: 99%
“…Finally, when time permits, the contra-lateral extremity should be carefully examined to both to detect injuries as well as to provide a normal control when uninjured. The clinician should attempt to detect an obvious cortical disruption, as this is the most reliable sign confirming a bony fracture, but other abnormalities should also be noted, including steps, axial deviations, periosteal lesions, hematomas, fluid collections, or any other softtissue changes [23]. The reported experience claims that there is no added distress or pain to the victim if care is taken by the examiner and US coupling gel is liberally applied [16,23].…”
Section: Scanning Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Color-coded duplex ultrasound or power Doppler ultrasound may be helpful in distinguishing symptomatic from noninflamed lesions. General Considerations Ultrasound evaluation of musculosceletal injuries represents an ideal supplementary investigation to radiography in children [37][38][39]. Many musculoskeletal injuries and disorders can be visualized using high-resolution sonography (Table 1).…”
Section: Miscellaneousmentioning
confidence: 99%